Gall stones and dyspepsia: does upper gastrointestinal endoscopy have a pivotal role? - Narayan, Harsha; Ravishankar, Nagaraj; Shivabasappa, Shivakumar; Kotekar, Nalini (International Surgery Journal, 2019)
Background: Asymptomatic gallbladder stones are often diagnosed as an incidental finding. Gallstone disease is asymptomatic in most patients diagnosed to have gall stone and cholecystectomy is considered to be the treatment of choice. However, less focus has been given to patient selection and to the symptoms of this disease in order to understand prevailing symptoms after surgery. Studies suggest that approximately 25% of patients undergoing cholecystectomy will not experience relief of symptoms, and that dyspeptic symptoms are least likely to be cured by cholecystectomy. Post-cholecystectomy syndrome (PCS) consists of a group of symptoms that persist after cholecystectomy. It is defined as early if occurring in the post-operative period and late if it manifests after months or years. The objectives of the study were to emphasize the importance of endoscopic evaluation as a routine pre-operative investigative tool in patients with dyspepsia and gall stones and evaluate the prevalence of dyspeptic symptoms in patients with gall stone disease. Methods: 92 patients with USG proven gall stones presenting with dyspepsia attending OPD or admitted in surgery department (JSS Hospital) were studied. Upper GI endoscopy was performed to detect for significant lesions. Results: Most common endoscopic finding was gastritis. Malignancy was found in 3 (3.3%) patients. The management plan was changed for 9 (13.6%) patients. Conclusions: Significant endoscopic findings were observed in 72.8% of patients. Routine pre-operative upper GI endoscopy is recommended in all patients with gall-stone disease who present with dyspepsia to avoid unnecessary cholecystectomy.